Practice in industry training in fish culture - Arce, Flerida M. (College of Fisheries, 1956)
The six months practice-in-industry training were spent mostly in actual fishpond work in the fishpond of Dr. Nable. Since my stay there, several improvements have been added to the fishpond. Observations were also done during my stay in that place. Several fishponds around the fishpond of Dr. Nable were surveyed. Each of these fishponds have different types of ayout methods of fishpond management being employed. There are also several fry grounds in the neighboring places. The supply of bangos fry that are being stocked in the fishpond of Dr. Nable come from the fry grounds of Sta. Teresa. Fishpond management as well as their constructions are very primitive. Most of the fishpond gates are made of wood. Only very few fishponds are equipped with concrete main water control gates. Harvesting of marketable bangos is done only when there is a full moon, because no offshore fishing vessels can go out to the sea to fish or they can fish but the amount caught is not enough to supply the consuming populace. There is a great demand for fishpond products at this period, so fishpond owners find it profitable to harvest their stock at full moon. Sites that are converted into fishponds are thickly vegetated with api-api and bakawan. Thick growth of api-api is an indication that the site will have thick growth of lumut. Experiment on bangos feed supplementation with the use of teramycin, vigofac, darak and lumut. Different combination of the feed supplement was used in each aquarium. Results not so good. Preservation of the fishpond product is also important. Some methods of fish preservation like making it into patis and bagoong is one of the easiest methods of preservation. The methods and procedures done in canning meat and other products is the same with that of canning fish.